Lipid phosphate phosphatase 3 regulates adipocyte sphingolipid synthesis, but not developmental adipogenesis or diet-induced obesity in mice. - Lorenzo Federico; Liping Yang; Jason Brandon; Manikandan Panchatcharam; Hongmei Ren; Paul Mueller; Manjula Sunkara; Diana Escalante-Alcalde; Andrew J Morris; Susan S Smyth (PLoS ONE, 2018)
Dephosphorylation of phosphatidic acid (PA) is the penultimate step in triglyceride synthesis. Adipocytes express soluble intracellular PA-specific phosphatases (Lipins) and broader specificity membrane-associated lipid phosphate phosphatases (LPPs) that can also dephosphorylate PA. Inactivation of lipin1 causes lipodystrophy in mice due to defective developmental adipogenesis. Triglyceride synthesis is diminished but not ablated by inactivation of lipin1 in differentiated adipocytes implicating other PA phosphatases in this process. To investigate the possible role of LPPs in adipocyte lipid metabolism and signaling we made mice with adipocyte-targeted inactivation of LPP3 encoded by the Plpp3(Ppap2b) gene. Adipocyte LPP3 deficiency resulted in blunted ceramide and sphingomyelin accumulation during diet-induced adipose tissue expansion, accumulation of the LPP3 substrate sphingosine 1- phosphate, and reduced expression of serine palmitoyl transferase. However, adiposity was unaffected by LPP3 deficiency on standard, high fat diet or Western diets, although Western diet-fed mice with adipocyte LPP3 deficiency exhibited improved glucose tolerance. Our results demonstrate functional compartmentalization of lipid phosphatase activity in adipocytes and identify an unexpected role for LPP3 in the regulation of diet-dependent sphingolipid synthesis that may impact on insulin signaling.